Domincans at Kingdom of Naples (13th-14th centuries): conflicts and political alignment - Teixeira, Igor Salomão (Horizonte, 2017)
This paper aims to present a general outline of the institution of the Order of the Preachers' convents in the Kingdom of Naples between the 13th and 14th centuries. Our documentation is composed of: Frederick II's Letter to the dominicans, the acts of the general and provincial Chapters, Bernard Gui's reports on the founding and division of convents in the provinces of the Order and pontifical documents (Papal bulls). Our method consists of three parts: characterizing the variety of documentation used; identify information on the institution of convents in Southern Italy and analyze data drawn from documentation in order to compose an approximate landscape of the possible relations of the friars and the angevin court with the Papacy. The historiography available was employed as a means of delimiting possible interpretations drawn from the data revealed by the chosen documentation. Our conclusion points to a complex articulation of Preachers, the House of Anjou and the Papacy, both in the conflagration as well as in the resolution of conflicts, mainly from 1260 onwards.